ETNOBOTANI MASYARAKAT DESA SAHAM (Studi Kasus di Desa Saham, Kecamatan Sengah Temila Kabupaten Landak, Kalimantan Barat) - Winda, Gregoria Wiraswati; Budhi, Setia; Sisillia, Lolyta (Universitas Tanjungpura, 2016)
District region of Landak has natural resources that is rich, either in the form of flora and fauna as well as natural scenery. Those are all natural resources with great potential to be developed for the welfare of the community.Methods of data collection is done through interviews and questionnaires to determine the respondents, The snowball sampling technique is also applied.The study was conducted in three phases, namely observation, interview, and literature study. From a research which is done on Desa Saham, there are 157 plant species included in 62 families. They consist of ; 100 species of food, 45 species of medicinal plants, 10 species of the dye matterial, 8 species of animal feed, 41 species ornamental plant, 6 species of aromatic herbs, 2 species of pesticide plant, 11 species of indigenous use, 7 species of firewood, and materials ropes, webbing, 12 species of craft material, and 3 species of building materials.Although thetraditional knowledgeof plants usedin the village ofshareshas decreased, the villagersstocksstillupholdtraditionalcultural valuesandknowledge, andare stilldoing sometraditionsrelatedto the respectof riceplants. Key words: Ethnobotany, snowball sampling, traditional knowledge.